2017
DOI: 10.1038/cdd.2017.58
|View full text |Cite
|
Sign up to set email alerts
|

When PERK inhibitors turn out to be new potent RIPK1 inhibitors: critical issues on the specificity and use of GSK2606414 and GSK2656157

Abstract: Accumulation of unfolded proteins in the endoplasmic reticulum (ER) causes a state of cellular stress known as ER stress. The cells respond to ER stress by activating the unfolded protein response (UPR), a signaling network emerging from the ER-anchored receptors IRE1α, PERK and ATF6. The UPR aims at restoring ER protein-folding homeostasis, but turns into a toxic signal when the stress is too severe or prolonged. Recent studies have demonstrated links between the UPR and inflammation. Consequently, small mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(130 citation statements)
references
References 43 publications
4
125
1
Order By: Relevance
“…Interestingly, oral administration of GSK2606414 alleviated neurodegeneration in tau transgenic mice [140]. However, a recent report suggested that GSK2606414 has a higher affinity for RIP kinases, in addition to generating serious side effects due to pancreatic toxicity [141]. In contrast, the administration of ISRIB provided neuroprotection in a model of prion disease while not triggering any pancreatic toxicity [50].…”
Section: Targeting the Upr For Therapeutic Inerventionmentioning
confidence: 99%
“…Interestingly, oral administration of GSK2606414 alleviated neurodegeneration in tau transgenic mice [140]. However, a recent report suggested that GSK2606414 has a higher affinity for RIP kinases, in addition to generating serious side effects due to pancreatic toxicity [141]. In contrast, the administration of ISRIB provided neuroprotection in a model of prion disease while not triggering any pancreatic toxicity [50].…”
Section: Targeting the Upr For Therapeutic Inerventionmentioning
confidence: 99%
“…Conversely, GSK-PKI treatment mildly increased apoptosis and dampened growth rate in cultured INS-1 cells (Fig 4B and C). This discrepancy may stem from pathway compensation in PERK KO cells or off-target GSK-PKI effects (48), but the aggregate effect is modest under low ER stress.…”
Section: Induced Apoptosis In Vitromentioning
confidence: 99%
“…PERK inhibition by these small molecules induced pancreatic β-cell toxicity, similar to what has been seen in the PERK knockout mouse, indicating more sophisticated methods to deliver these inhibitors are required (140).…”
Section: Amg Perk44mentioning
confidence: 77%